The resistive region of pulmonary microvessels in ovalbumin-sensitised guinea pigs: a quantitative and qualitative histological study - Popko, S. S.; Yevtushenko, V. M.; Kaplaushenko, A. H.; Tertishniy, S. I.; Попко, Світлана Сергіївна; Євтушенко, Валентина Михайлівна; Каплаушенко, Андрій Григорович; Тертишний, Сергій Ігорович (My University, 2022)
This work aimed to study the morphofunctional changes in the resistive region of the pulmonary microcirculatory bed in ovalbumin- sensitised guinea pigs. Using histological, morphometric, and statistical methods, we studied the lungs of 48 male guinea pigs in conditions of the experimental allergic inflammatory process. To assess the structural and functional state of medium (51– 125 μm) and small (25–50 μm) arterioles, the outer and inner diameters, the thickness of the tunica media, and the Kernogan index were determined. The most pronounced changes, such as thickening of their walls and narrowing of the lumen in the late stages of the allergic inflammatory process, consisted in the restructuring of medium arterioles. Compared to control animals, the inner diameter of the medium arterioles decreased three times (p*/**<0.05) in experimental group 4; the thickness of the tunica media of medium arterioles increased two times (p*/**<0.05) in experimental group 3. These changes are the result of the increasing tone and hypertrophy of the smooth muscles of the tunica media and the decreasing capacity of arterioles as evidenced by a statistically significant increase of the Kernogan index-indicated hypertrophy and the increasing tone of the smooth muscles of the tunica media and decreasing vascular throughput. Šio darbo tikslas buvo ištirti ovalbuminui įjautrintų jūrų kiaulyčių plaučių mikrocirkuliacijos vagos rezistencinės jungties morfofunkcinius pokyčius. Ištyrėme 48 jūrų kiaulyčių patinų plaučius histologiniais, morfometriniais ir statistiniais metodais eksperimentinio alerginio uždegiminio proceso sąlygomis. Siekiant įvertinti vidutinių (51–125 μm) ir mažų (25–50 μm) arteriolių struktūrinę ir funkcinę būklę, nustatytas išorinis ir vidinis skersmuo, tunikos terpės storis ir Kernogano indeksas. Labiausiai pakito vidutinės arteriolės: užfiksuotas jų sienelių sustorėjimas ir spindžio susiaurėjimas vėlyvose alerginio uždegiminio proceso stadijose. Lyginant su kontroliniais gyvūnais, ketvirtos eksperimentinės grupės vidutinių arteriolių vidinis skersmuo sumažėjo 3 kartus (p*/** < 0,05), o trečios eksperimentinės grupės vidutinių arteriolių tunikos terpės storis padidėjo 2 kartus (p*/** < 0,05). Statistiškai reikšmingai padidėjęs Kernogano indeksas rodo, kad šiuos pokyčius lemia lygiųjų raumenų tunikos terpės hipertrofija ir didesnis tonusas bei mažėjantis kraujagyslių pralaidumas.
Ovalbuminui įjautrintų jūrų kiaulyčių plaučių mikrokraujagyslių rezistencinė sritis: kiekybinė ir kokybinė histologinė analizė
S. Popko - https://orcid.org/0000-0002-5533-4556; V. Yevtushenko - https://orcid.org/0000-0002-6858-6488; A. Kaplaushenko - https://orcid.org/0000-0003-3704-5539; S. Tertishniy - http://orcid.org/0000-0003-3856-4234.
Keywords: arteriole; microcirculation; experimental allergic inflammation; lung; ovalbumin; guinea pig; arteriolė; mikrocirkuliacija; eksperimentinis alerginis uždegimas; plaučiai; ovalbuminas; jūrų kiaulytė